The Curvilinear Relationship Between Career Calling and Work Fatigue: A Moderated Mediating Model - Zhou, Jie; Zhang, Jian wei; Xuan, Xing yu (Frontiers in Psychology, 2020)
Drawing on the job demands-resources (JD-R) model and event system theory (EST), this study constructed a moderated mediating model to investigate the direct effect of career calling on work fatigue, the mediating effect of role overload, and the moderating effect of COVID-19 event disruption in the above relationships. We administered an online questionnaire to 488 Chinese police officers who participated in frontline work to prevent and control the COVID-19 pandemic. The results showed a U-shaped curvilinear relationship of career calling with physical fatigue, mental fatigue, emotional fatigue, and role overload. Moreover, role overload partially mediated these curvilinear relationships. In addition, COVID-19 event disruption positively moderated the direct curvilinear effect of career calling on role overload, physical fatigue, and emotional fatigue, as well as the first stage of the mediating effect in the relationship between career calling and physical, mental, and emotional fatigue through role overload. Furthermore, the direct U-shaped curvilinear effects and the indirect effects were more significant when COVID-19 event disruption was high.